Histomorphological Variants of Squamous Cell Carcinoma in Upper Aero-digestive Tract - Hijab Shah, Soffia Khursheed, Ammara Ijaz (Journal of Rawalpindi Medical College, 2018)
Background: To determine the site wise frequency of squamous cell carcinoma variants in upper aerodigestive tract. Methods: In this observational study all the cases of diagnosed squamous cell carcinoma of upper aero digestive tract were included. All the cases were formalin fixed and processed routinely to form paraffin blocks. Slides were made and stained with H&E. Results: Out of 41 cases, 33 cases showed the classic pattern of squamous cell carcinoma, which arose from Oral cavity, alveolar ridge, tongue, oesophagus, palate, pharynx, nose, larynx and bronchus. Most of the classic squamous cell carcinomas were of keratinizing type. Conclusions: Majority of cases of squamous cell carcinomas in upper aero-digestive tract revealed classical pattern .